An efficient synthesis of [1, 3]dioxolo[4, 5-g]thieno[3, 4-b]quinolin-8(5H)-ones as novel thiazapodophyllotoxin analogues with potential anticancer activity. Issue 7 (1st April 2015) - Li, Tuanjie; Lu, Ting; Yu, Chenxia; Yao, Changsheng
Graphical abstract: Abstract: A catalyst-free synthesis of 6, 9-dihydro-[1, 3]dioxolo[4, 5- g ]thieno[3, 4- b ]quinolin-8(5 H )-ones as novel analogues of podophyllotoxins was developed by a three-component reaction of aldehydes, ethyl 2, 4-dioxotetrahydrothiophene-3-carboxylate and 3, 4-(methylenedioxy)aniline. This methodology not only provides new chemical library for the screening of anticancer activity, but also features excellent isolated yields, short reaction time, simple work up procedure and little environmental impact.